PENGARUH PENGGUNAAN TEKNOLOGI INFORMASI DALAM MANAJEMEN PERENCANAAN PENDIDIKAN UNTUK MENINGKATKAN EFISIENSI PENDIDIKAN - Indri Febrianti; Jihan Tuffahati; Ahmad Rifai; Rizky Hasan Affandi; Syakila Pradita; Rizki Akmalia; Amiruddin Siahaan (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The use of information technology has changed the way we carry out various aspects of life, including in the education sector. In this digital era, the use of news technology in educational planning management has brought considerable changes and various benefits. This study aims to determine how the influence of the use of information technology in the management of educational planning to increase educational efficiency. The research method used is the library research method, which involves collecting data and information from various sources of literature that are relevant to the research topic. This research will identify and analyze various challenges and obstacles in the use of information technology in educational planning management and the solutions offered to overcome them. In addition, this study will also analyze the impact of using information technology in increasing educational efficiency. The results of this study are expected to provide a better understanding of the potential use of information technology in increasing educational efficiency and its benefits. The findings of this study are expected to be the basis for decision making and strategic planning in the implementation of information technology in education management, with the ultimate goal of improving the overall quality of education.